Design and analysis of triangular array antenna for UHF RFID reader - Muhammad Firdaus, Zawawi; Mohd Hisyam, Mohd Ariff; Mohammad Fadhil, Abas; Rahimah, Jusoh (AIP Publishing, 2025)
In this paper, the purpose of this study is to design and analysis the triangular array microstrip patch antenna for application of Radio Frequency (RFID) Ultra High Frequency (UHF). Array antennas are used in RFID application as it offers high gain and directivity to allow a long distance read range. The microstrip patch is arranged in 2 x 2 array and material used is FR-4 with dielectric constant 4.7 and height of 0.16 cm. Design of antenna patch 919 MHz to 923 MHz is designed, built, and measured for UHF RFID application in Malaysia. Fundamentals theory and calculation studies are conducted to analysis the changes and effect in dimension in radio frequency identification RFID antenna. The antenna simulation was run using the CST Studio Suite 2019 as the primary software to model, simulate the results, there are a few parameters that going to be analyze which includes reflection coefficient (S11), Voltage Standing Ratio (VSWR), directivity, gain, radiation pattern and bandwidth.